Solve for x, y
x=\frac{\sqrt{14}+12}{5}\approx 3.148331477\text{, }y=\frac{6-2\sqrt{14}}{5}\approx -0.296662955
x=\frac{12-\sqrt{14}}{5}\approx 1.651668523\text{, }y=\frac{2\sqrt{14}+6}{5}\approx 2.696662955
Graph
Share
Copied to clipboard
2x+y=6,y^{2}+x^{2}=10
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
2x+y=6
Solve 2x+y=6 for x by isolating x on the left hand side of the equal sign.
2x=-y+6
Subtract y from both sides of the equation.
x=-\frac{1}{2}y+3
Divide both sides by 2.
y^{2}+\left(-\frac{1}{2}y+3\right)^{2}=10
Substitute -\frac{1}{2}y+3 for x in the other equation, y^{2}+x^{2}=10.
y^{2}+\frac{1}{4}y^{2}-3y+9=10
Square -\frac{1}{2}y+3.
\frac{5}{4}y^{2}-3y+9=10
Add y^{2} to \frac{1}{4}y^{2}.
\frac{5}{4}y^{2}-3y-1=0
Subtract 10 from both sides of the equation.
y=\frac{-\left(-3\right)±\sqrt{\left(-3\right)^{2}-4\times \frac{5}{4}\left(-1\right)}}{2\times \frac{5}{4}}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1+1\left(-\frac{1}{2}\right)^{2} for a, 1\times 3\left(-\frac{1}{2}\right)\times 2 for b, and -1 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
y=\frac{-\left(-3\right)±\sqrt{9-4\times \frac{5}{4}\left(-1\right)}}{2\times \frac{5}{4}}
Square 1\times 3\left(-\frac{1}{2}\right)\times 2.
y=\frac{-\left(-3\right)±\sqrt{9-5\left(-1\right)}}{2\times \frac{5}{4}}
Multiply -4 times 1+1\left(-\frac{1}{2}\right)^{2}.
y=\frac{-\left(-3\right)±\sqrt{9+5}}{2\times \frac{5}{4}}
Multiply -5 times -1.
y=\frac{-\left(-3\right)±\sqrt{14}}{2\times \frac{5}{4}}
Add 9 to 5.
y=\frac{3±\sqrt{14}}{2\times \frac{5}{4}}
The opposite of 1\times 3\left(-\frac{1}{2}\right)\times 2 is 3.
y=\frac{3±\sqrt{14}}{\frac{5}{2}}
Multiply 2 times 1+1\left(-\frac{1}{2}\right)^{2}.
y=\frac{\sqrt{14}+3}{\frac{5}{2}}
Now solve the equation y=\frac{3±\sqrt{14}}{\frac{5}{2}} when ± is plus. Add 3 to \sqrt{14}.
y=\frac{2\sqrt{14}+6}{5}
Divide 3+\sqrt{14} by \frac{5}{2} by multiplying 3+\sqrt{14} by the reciprocal of \frac{5}{2}.
y=\frac{3-\sqrt{14}}{\frac{5}{2}}
Now solve the equation y=\frac{3±\sqrt{14}}{\frac{5}{2}} when ± is minus. Subtract \sqrt{14} from 3.
y=\frac{6-2\sqrt{14}}{5}
Divide 3-\sqrt{14} by \frac{5}{2} by multiplying 3-\sqrt{14} by the reciprocal of \frac{5}{2}.
x=-\frac{1}{2}\times \frac{2\sqrt{14}+6}{5}+3
There are two solutions for y: \frac{6+2\sqrt{14}}{5} and \frac{6-2\sqrt{14}}{5}. Substitute \frac{6+2\sqrt{14}}{5} for y in the equation x=-\frac{1}{2}y+3 to find the corresponding solution for x that satisfies both equations.
x=-\frac{2\sqrt{14}+6}{2\times 5}+3
Multiply -\frac{1}{2} times \frac{6+2\sqrt{14}}{5}.
x=-\frac{1}{2}\times \frac{6-2\sqrt{14}}{5}+3
Now substitute \frac{6-2\sqrt{14}}{5} for y in the equation x=-\frac{1}{2}y+3 and solve to find the corresponding solution for x that satisfies both equations.
x=-\frac{6-2\sqrt{14}}{2\times 5}+3
Multiply -\frac{1}{2} times \frac{6-2\sqrt{14}}{5}.
x=-\frac{2\sqrt{14}+6}{2\times 5}+3,y=\frac{2\sqrt{14}+6}{5}\text{ or }x=-\frac{6-2\sqrt{14}}{2\times 5}+3,y=\frac{6-2\sqrt{14}}{5}
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}